1989
DOI: 10.1002/1097-0142(19891215)64:12<2493::aid-cncr2820641215>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of monoclonal antibodies can distinguish primary lung tumors from metastatic lung tumors sampled by fine needle aspiration biopsy

Abstract: MARCELLA MOTTOLESE, PHD, IRENE VENTURO, MD, MASSIMO RINALDI, MD, NORBERT0 CAMPIONI, MD, ANTONELLO ALUFFI, MD, CORRADO GALL0 CURCIO, MD, RAFFAELE PERRONE DONNORSO, MD, AND PIER GlORGlO NATALI, MD Transthoracic fine needle aspiration (FNA) biopsies performed under computed tomography (CT) scan (CT-FNA) have greatly improved the cytodiagnosis of lung tumors. However, the distinction between a primary lesion and a metastatic lesion still may be difficult on the basis of morphologic criteria. To evaluate whether a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Therefore, a significant number of cases cannot be diagnosed beyond the general term of 'adenocarcinoma' and 'carcinoma' until the histological examination becomes available (Giardini et al, 1993;Van der Gaast et al, 1996). Because previous studies of ours have shown that the combined evaluation of a large and well-characterized panel of MAbs on cytological specimens has the capability of detecting tumour origin in patients with cryptic tumours (Mottolese et al, 1988(Mottolese et al, , 1989(Mottolese et al, , 1990(Mottolese et al, , 1994, we have routinely used this selected combination of reagents to establish more critically the diagnostic accuracy of the method in identifying otherwise undiagnosed SPTs. The results of this study, which reports our experience over the last 5 years, clearly demonstrate that this diagnostic approach offers an unprecedented accuracy in detecting SPTs, mainly in those lesions clearly malignant on the basis of cytological features, in which an undifferentiated morphology cannot permit establishment of their primary or metastatic nature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a significant number of cases cannot be diagnosed beyond the general term of 'adenocarcinoma' and 'carcinoma' until the histological examination becomes available (Giardini et al, 1993;Van der Gaast et al, 1996). Because previous studies of ours have shown that the combined evaluation of a large and well-characterized panel of MAbs on cytological specimens has the capability of detecting tumour origin in patients with cryptic tumours (Mottolese et al, 1988(Mottolese et al, , 1989(Mottolese et al, , 1990(Mottolese et al, , 1994, we have routinely used this selected combination of reagents to establish more critically the diagnostic accuracy of the method in identifying otherwise undiagnosed SPTs. The results of this study, which reports our experience over the last 5 years, clearly demonstrate that this diagnostic approach offers an unprecedented accuracy in detecting SPTs, mainly in those lesions clearly malignant on the basis of cytological features, in which an undifferentiated morphology cannot permit establishment of their primary or metastatic nature.…”
Section: Discussionmentioning
confidence: 99%
“…aSee Mottolese et al (1988Mottolese et al ( , 1989Mottolese et al ( , 1990Mottolese et al ( , 1993Mottolese et al ( , 1994. b NS, not significant to detect tumour origin.…”
Section: Preparation Of Cell Substratesmentioning
confidence: 99%
See 1 more Smart Citation